Monolayer graphene on nanostructured Ag for enhancement of surface-enhanced Raman scattering stable platform. (6th March 2015) - Dai, Zhigao; Mei, Fei; Xiao, Xiangheng; Liao, Lei; Wu, Wei; Zhang, Yupeng; Ying, Jianjian; Wang, Lingbo; Ren, Feng; Jiang, Changzhong
Abstract: We have reported that the Ag nanostructure-based substrate is particularly suitable for surface-enhanced Raman scattering when it is coated with monolayer graphene, an optically transparent and chemistry-inertness material in the visible range. Ag bowtie nanoantenna arrays and Ag nanogrids were fabricated using plasma-assisted nanosphere lithography. Our measurements show that atmospheric sulfur containing compounds are powerless to break in the monolayer graphene to vulcanize the surfaces of the Ag bowtie nanoantenna arrays and Ag nanogrids by various means, including scanning electron microscopy (SEM) and x-ray photoelectron spectroscopy (XPS). Furthermore, the Ag nanostructure substrate coated with the monolayer graphene film shows a larger enhancement of Raman activity and the electromagnetic field than the uncoated substrate. Compared with those of bare Ag nanostructures, the averaged EFs of graphene-film-coated Ag nanostructures were estimated to be about 21 and 5 for Ag bowtie nanoantenna arrays and nanogrids after one month later in air, respectively. These observations are further supported by theoretical calculations.